Prevention of Cryptosporidium and GIARDIA at the Human/Gorilla/Livestock Interface - Gladys Kalema-Zikusoka; Stephen Rubanga; Birungi Mutahunga; Ryan Sadler (Frontiers Media S.A., 2018)
Mountain gorillas (Gorilla beringei beringei) are critically endangered and found in Bwindi Impenetrable Forest and Virunga Volcanoes. Habitat destruction, high human population growth rates, poverty, and disease are threatening the survival of mountain gorillas. A study implemented in 2010 investigated the prevalence of Cryptosporidium and Giardia sps., as part of a long-term gorilla health-monitoring program at Bwindi through regular fecal sample collection, and comparative pathogen analysis at the human/gorilla/livestock interface. Samples collected from habituated and non-habituated gorillas, community-owned livestock herds and people at Bwindi were screened for Cryptosporidium and Giardia sps. using ImmunoSTAT Commercial Field Kit and doubtful samples confirmed with Direct Fluorescence Antibody Test (DFA). Giardia was found in 5.5% of livestock, 40% of symptomatic humans from the local hospital and 9.5% of asymptomatic park staff, but not in gorillas. Cryptosporidium was found in 3.1% of habituated gorillas, 4.7% of livestock, and 62.4% of park staff. Whereas, previous studies have compared Cryptosporidium and Giardia sps. in gorillas and livestock, this is the first study making a comparison in humans, gorillas and livestock. Unlike previous studies in Bwindi and Virungas, no Giardia sp. was found in gorillas. The improving hygiene and sanitation of local communities sharing a habitat with gorillas through Village Health and Conservation Teams (VHCTs) established in 2007, could have contributed to the decreased prevalence of Giardia in this mountain gorilla population. Cryptosporidium sp. only found in the habituated gorillas could be associated with human interaction, similar to previous studies. A subsequent VHCT was selected for each village with positive human samples and where gorillas often range, local health centers were mobilized to educate patients on the health risks of collecting water from unprotected sources and cattle water troughs were built. This paper describes a One Health approach to reducing cross species disease transmission at the human/gorilla/livestock interface.